Critical behavior of majority vote model on two-dimensional quasiperiodic tilings. (23rd January 2019) - Alves, T F A; Lima, F W S; Macedo-Filho, A; Alves, G A
Abstract: We investigated majority vote model coupled with quasiperiodic tilings by using both Monte Carlo and finite size scaling techniques. We obtained numerically the following averages: Binder cumulant, order parameter, defined as the averaged opinion balance, and its respective susceptibility . Our numerical results suggest that the system falls in two-dimensional Ising universality class. In addition, our results are in agreement with Harris–Barghathi–Vojta criterion, which states that two-dimensional quasiperiodic ordering is irrelevant and does not change any of the critical exponents.